Evaluasi tingkat kepuasan pasien terhadap pelayanan kefarmasian di Rumah Sakit X Tangerang Selatan - Fahriati, Andriyani Rahmah; Andani, Deawuri; Sucipto, Sucipto (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Sarjana Farmasi Indonesia (ISFI), 2024)
Background: Improving the quality of services and the health care system provided to patients will be the main choice for patients to come to visit the hospital, one of which is inseparable from the service system at the hospital is pharmaceutical services. Measuring the level of patient satisfaction with services can be measured by the SERVQUAL (Service Quality) method, this method is used by making a comprehensive customer satisfaction assessment survey for services in the field of goods and services, in this case pharmaceutical services. The formulation of the problem in this study was to find out how the patient's satisfaction with pharmaceutical services at Hospital X Tangerang Selatan period January - March 2020. Purpose: To determine patient satisfaction with pharmaceutical services at X Hospital, South Tangerang. Methods: This research is a descriptive non-experimental research and processed quantitatively analytically with a survey approach. The validity and reliability test of the questionnaire was carried out on 30 respondents and the data analysis used the calculation of the total service quality index. The population in this study were all patients who visited the pharmacy installation at Hospital X Tangerang Selatan in the period January – March 2020. There were 100 patients who met the inclusion criteria, including being willing to become respondents, able to read and write, aged over 15 years, and ever received services at the pharmacy installation of RS X South Tangerang. Results: The percentage of each variable obtained is an average of 82.06% which is categorized as the results of the evaluation of patient satisfaction with the quality of pharmaceutical services provided that are very satisfied, with the details of each dimension, namely the reliability dimension, which is 78.23% of patients stated satisfied, on the responsiveness dimension 79,95% of patients said they were satisfied, on the dimension of assurance 82,5% of patients said they were very satisfied, on the empathy dimension 86,1% of patients said they were very satisfied, and on the direct evidence dimension 83,52% of patients said they were very satisfied. Conclusion: The level of patient satisfaction with outpatient pharmacy services at Hospital X, which is seen on the five dimensions of servqual, the results are very satisfied, although there are dimensions that need to be improved, especially in the category of information on how to store drugs and drug side effects and delivery of drugs in a timely manner. on time, this must be evaluated again so that it can be further improved in its services. Keywords: evaluation; satisfaction; pharmaceutical services; SERVQUAL Pendahuluan: Peningkatan mutu layanan dan sistem layanan kesehatan yang diberikan kepada pasien akan menjadi pilihan utama bagi pasien untuk datang berkunjung di Rumah Sakit, salah satu yang tidak terpisahkan dari sistem pelayanan di Rumah Sakit adalah Pelayanan kefarmasian. Pengukuran tingkat kepuasan pasien terhadap pelayanan dapat diukur dengan metode SERVQUAL (Service Quality), metode ini digunakan dengan cara membuat survei penilaian kepuasan pelanggan secara komprehensif bagi pelayanan dibidang barang dan jasa, dalam hal ini adalah pelayanan kefarmasian. Rumusan permasalah dalam penelitian ini adalah untuk mengetahui bagaimana kepuasan pasien terhadap pelayanan kefarmasian di Rumah Sakit X Tangerang Selatan periode Januari – Maret 2020. Tujuan: Untuk mengetahui kepuasan pasien terhadap pelayanan kefarmasian di Rumah Sakit X Tangerang Selatan. Metode: Penelitian ini merupakan penelitian non ekperimental deskriptif dan diolah secara analitik kuantitatif dengan pendekatan survei. Uji validitas dan reabilitas kuesioner dilakukan terhadap 30 responden dan analisis data menggunakan perhitungan indeks total kualitas pelayanan. Populasi dalam penelitian ini adalah seluruh pasien yang berkunjung ke instlasi farmasi di Rumah Sakit X Tangerang Selatan pada periode Januari – Maret 2020. Terdapat 100 pasien yang telah memenuhi kriteria inklusi antara lain bersedia menjadi responden, bisa baca dan tulis, berusia diatas 15 tahun, dan pernah mendapatkan pelayanan di instalasi farmasi RS X Tangerang Selatan. Hasil: Diperoleh presentase tiap variable didapat rata-rata 82,06% yang dikategorikan hasil evaluasi kepuasan pasien terhadap kualitas pelayanan kefarmasian yang diberikan sudah sangat puas, dengan perincian masing-masing dimensi yakni pada dimensi kehandalan yakni sebesar 78,23% pasien menyatakan puas, pada dimensi daya tanggap 79,95% pasien menyatakan puas, pada dimensi jaminan 82,5% pasien menyatakan sangat puas, pada dimensi empati 86,1% pasien menyatakan sangat puas, dan pada dimensi bukti langsung 83,52% pasien menyatakan sangat puas. Simpulan: Tingkat kepuasan pasien terhadap pelayanan kefarmasian rawat jalan Rumah Sakit X, yang dilihat pada lima dimensi servqual, diperoleh hasil bahwa sudah sangat puas, walaupun ada dimensi yang perlu tetap ditingkatkan terutama pada kategori informasi cara penyimpanan obat dan efek samping obat serta penyerahan obat secara tepat waktu, hal ini yang harus di evaluasi lagi agar dapat lebih ditingkatkan dalam pelayanannya. Kata Kunci : Evaluasi; kepuasan; pelayanan kefarmasian; SERVQUAL